Experiences of early air travel with pneumothorax after anterior spinal surgery - Amy Yoke Foong Wong; Choong Hoon Foo; Chung Chek Wong; Khin Maung Ohn (BMJ, 2021)
Anterior thoracic or thoracolumbar spinal surgery by retropleural approach always carries a risk of pneumothorax as its consequence. Conventionally, the Aerospace Medicine Association and the British Thoracic Society recommend 2 weeks delay of air travel for a patient with resolved postoperative pneumothorax. They also label active pneumothorax as an absolute contraindication for commercial air travel. Such a delay always causes psychological and financial stress to patients and family who are far from home. Here, we report three patients with postoperative pneumothorax, who insisted on early air travel despite being informed of the possible consequences.